High-sensitive Biomarkers of Blood Antiradical Activity in Mice Exposed to γ-irradiation - Kalmakhelidze, S.; Sanikidze, T.; Topuria, D.; Chkhikvishvili, I.; Shekiladze, E.; Ivanishvilli, N.; Gogebashvili, M.; Lomadze, E.; Ormotsadze, G. (International Journal of Innovative Research in Medical Science, 2021)
Diagnostic markers are important indicators for the assessment of the possible consequences of radiation exposure, which could lead to acute and chronic radiation toxicity. The goal of the study is to determine high-sensitive markers of blood redox status in relation to the dose of radiation. The mice were exposed to γ-irradiation (Cs137) at a total dose of 3, 5, and 7Gy. After 1, 2, 7, and 14 days of the irradiation, the blood samples were drawn under ether anesthesia from the inferior vena cava and the activity of antioxidant system (enzymatic -superoxide dismutase (SOD), catalase) and non-enzymatic total antioxidant activity (TAA) of blood serum was determined. The results of our investigation support the fact that the non-enzymatic antioxidant TAA plays an important role in the prevention of radiation damage during ionizing radiation exposure, which makes it possible to consider TAA as a promising candidate as the biomarker of radiation dose.